2020
DOI: 10.1038/s41589-020-00689-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Mpro inhibitors and activity-based probes for patient-sample imaging

Abstract: Substrate specificity of SARS-CoV and SARS-CoV-2 M pro s. To determine the SARS-CoV M pro and SARS-CoV-2 M pro substrate preferences, we applied a HyCoSuL approach. The library consists of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
368
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(392 citation statements)
references
References 36 publications
14
368
0
10
Order By: Relevance
“…In conclusion, inhibition of the M pro and PL pro proteases is considered to be a potentially activity in cells 26,37 . In this work, we describe our efforts to screen a library of approximately 650 diverse covalent inhibitor scaffolds against the two primary SARS-CoV-2 cysteine proteases, M pro and PL pro .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In conclusion, inhibition of the M pro and PL pro proteases is considered to be a potentially activity in cells 26,37 . In this work, we describe our efforts to screen a library of approximately 650 diverse covalent inhibitor scaffolds against the two primary SARS-CoV-2 cysteine proteases, M pro and PL pro .…”
Section: Resultsmentioning
confidence: 90%
“…To identify potential inhibitors of M pro and PL pro , we developed fluorogenic substrate assays that allowed us to screen a focused library of cysteine reactive molecules. We based the design of internally quenched-fluorescent M pro substrates on recent specificity profiling of the P1-4 residues using non-natural amino acids with a C-terminal 7-amino-4-carbamoylmethylcoumarin (ACC) reporter 26 . However, because the reported structures have relatively low turnover rates, we decided to make extended versions of these substrates that combine the optimal P1-4 residues with the native cleavage consensus of the P1'-P3' residues (i.e., residues C-terminal of the scissile bond) 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…The benzyl ring of the α-methylbenzyl moiety is partially positioned both in the S2 and S3 pockets, a novel binding pose that has not been observed with existing M pro inhibitors. Normally, a substituent at this position would be expected to flip away from the enzyme core towards the solvent-exposed S3 pocket, which explains why P3 substitutions have little to no influence on the enzymatic inhibition 4 . However, the hydrophobic nature of the benzyl ring in 23R causes it to project towards the core near the S2 pocket, forcing Gln189 to rotate outwards (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…M pro is a cysteine protease encoded in the viral polyprotein as non-structural protein 5 (Nsp5) that cleaves the viral polyproteins pp1a and pp1ab at more than 11 sites. Despite its multiple proteolytic sites, M pro was shown to have a high substrate specificity of glutamine at the P1 position 4 . As such, the majority of the reported M pro inhibitors were designed to contain a 2-pyrrolidone at the P1 substitution as a mimetic of the glutamine in the substrate 5 .…”
mentioning
confidence: 99%
“…1e), speci cally, Leu27, Asn119, and Gly146 are near the catalytic dyad (His41 and Cys145). They may provide some support to the catalytic center, as evidenced by a recent study, in which Leu27 was found to play a key role in the activity of the M pro structure of SARS-CoV2 7 . Whereas, Leu27 and Asn119 are involved in the formation of the binding site in SARS-CoV M pro 16 (Table 1).…”
mentioning
confidence: 92%